2009
DOI: 10.14430/arctic265
|View full text |Cite
|
Sign up to set email alerts
|

Community Monitoring of Environmental Change: College-Based Limnological Studies at Crazy Lake (Tasirluk), Nunavut

Abstract: ABSTRACT. In light of the difficult logistics and high cost of polar research into climate change, involvement of local people can contribute immensely to important data collection. One can use the knowledge and skills of human resources that are already present-teachers, students, and community members. An example is the long-term Arctic monitoring program established at Crazy Lake (63˚51' N, 68˚28' W) near Iqaluit, Nunavut, to monitor snow and ice thickness, biological components, and water chemistry. Nunavu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In Churchill, MB (58.72°N, 93.78°W), the measured premelt percentage of white to total ice for Malcolm Ramsey Lake was 16% in 2009 and 6% in 2010 (field data used in Brown & Duguay, ). Further north, Dyck () found that white ice represented only 7% of total ice cover during the winter of 2005–2006 on Baffin Island, NU (63.51°N, 68.28°W), whereas further north yet in the High Arctic on Small Lake, near Resolute, NU (74.35°N, 95.05°W), white ice cover represented <4% of the total ice thickness measured in an auger hole during May 2016 (Brown, unpublished data), clearly showing the stark difference in composition of northern lake ice to temperate lake ice.…”
Section: Discussionmentioning
confidence: 99%
“…In Churchill, MB (58.72°N, 93.78°W), the measured premelt percentage of white to total ice for Malcolm Ramsey Lake was 16% in 2009 and 6% in 2010 (field data used in Brown & Duguay, ). Further north, Dyck () found that white ice represented only 7% of total ice cover during the winter of 2005–2006 on Baffin Island, NU (63.51°N, 68.28°W), whereas further north yet in the High Arctic on Small Lake, near Resolute, NU (74.35°N, 95.05°W), white ice cover represented <4% of the total ice thickness measured in an auger hole during May 2016 (Brown, unpublished data), clearly showing the stark difference in composition of northern lake ice to temperate lake ice.…”
Section: Discussionmentioning
confidence: 99%
“…Snow ice measurements are not recorded in the historical archives, however a study on Baffin Island near Iqaluit, Nunavut, found a 7 % ratio of snow ice to maximum ice thickness during the 2005-2006 winter (Dyck, 2007). The 1961-1990 mean ratio in this area was ∼6 %.…”
Section: Validation Of Ice Phenology and Thicknessmentioning
confidence: 95%
“…Two studies identify the importance of government-level adaptation interventions to address barriers to adaptation and drivers of emerging vulnerabilities, arguing that impacts of climate change can be managed with appropriate intervention and support mechanisms (Ford et al, 2007(Ford et al, , 2010a. Other projects have sought to build adaptive capacity through actively engaging communities in research, which includes integrated community-based monitoring networks to facilitate greater sharing between communities regarding travel conditions (Gearheard et al, 2006;Tremblay et al, 2006Tremblay et al, , 2008Huntington et al, 2009;Weatherhead et al, 2010), environmental change monitoring (Dyck, 2007), and open houses to increase understanding of scientific research and findings (Hanesiak et al, 2010).…”
Section: Infrastructure and Transportationmentioning
confidence: 99%